Evaluating the Therapeutic Effect of Taichong (LR3) and Zusanli (ST36) on Hypertension in the Elderly - I Dewa Ayu Agra Darmawati; Ida Ayu Anom Rastiti; Ida Ayu Suptika Strisanti (Jurnal Keterapian Fisik, 2025)
Background: Hypertension is a health problem commonly experienced by the elderly and is one of the most prevalent conditions in this age group. The effect of acupuncture in lowering blood pressure includes regulating vasoactive substances in the blood vessel endothelium. One of the active substances known to be affected by release and activation through acupuncture is Nitric Oxide (NO). This study aimed to determine the effectiveness of taichong and zusanli points of acupuncture for hypertension patients. Methods: This study employed a one-group pre-test–post-test pre-experimental design involving 40 elderly participants selected through accidental sampling during an elderly exercise program. Acupuncture intervention was performed on the LR3 and ST36 points according to clinical guidelines for 10 minutes per session by certified practitioners, with close monitoring and no reported side effects. Data were analyzed using SPSS version 22, and post-intervention comparisons were conducted using paired samples t-test.  Results: The analysis showed a reduction in mean systolic blood pressure of 10.95 mmHg after the acupuncture intervention (95% CI: 155.53 to 165.87, p-value < 0.01), indicating a statistically significant pre–post difference within the sample. In contrast, the mean diastolic blood pressure decreased by 1.15 mmHg (95% CI: 76.76 to 84.19, p-value > 0.05), suggesting no statistically significant change.  Conclusion: These findings reflect an improvement in systolic, but not diastolic, blood pressure among the participating elderly individuals. Acupuncture shows potential as a supportive therapy in lowering systolic blood pressure in the elderly.